2016
DOI: 10.1371/journal.pone.0153025
|View full text |Cite
|
Sign up to set email alerts
|

Co-Targeting of JNK and HUNK in Resistant HER2-Positive Breast Cancer

Abstract: Strategies for successful primary treatment of HER2-positive breast cancer include use of the HER2 inhibitors trastuzumab or lapatinib in combination with standard chemotherapy. While successful, many patients develop resistance to these HER2 inhibitors indicating an unmet need. Consequently, current research efforts are geared toward understanding mechanisms of resistance and the signaling modalities that regulate these mechanisms. We have undertaken a study to examine whether signaling molecules downstream o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…In GC, the pivotal role of HER2 metastasis has been shown[6,29], but not much is known about the downstream effectors in this process. Although most studies have implicated AKT and ERK as promising therapeutic targets for HER2-positive tumors[27,28,30], JNK, especially in breast cancer, is now emerging as an important molecule in HER2 signaling pathways[11,12]. In the present study, we found positive associations between HER2, JNK and AKT in terms of GC metastasis.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In GC, the pivotal role of HER2 metastasis has been shown[6,29], but not much is known about the downstream effectors in this process. Although most studies have implicated AKT and ERK as promising therapeutic targets for HER2-positive tumors[27,28,30], JNK, especially in breast cancer, is now emerging as an important molecule in HER2 signaling pathways[11,12]. In the present study, we found positive associations between HER2, JNK and AKT in terms of GC metastasis.…”
Section: Discussionsupporting
confidence: 48%
“…In general, JNK has been established as a key kinase in cancer cell apoptosis[10]. Recently, the role of JNK in HER2 signaling pathway has gained much attention, because JNK activation plays a critical role in the lapatinib-resistance in HER2-positve breast cancer cells[11,12]. However, regarding GC, the biological significance of JNK in relation to HER2 signaling has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is currently unknown if EGFR can independently regulate Hunk or if this effect on Hunk expression is due to the dimerization between HER2/ErbB2 and EGFR. Most recently, it has been reported that Hunk knockdown is able to inhibit EGFR activity indicated by reduced EGFR phosphorylation in HER2 + /ErbB2 + breast cancer cells resistant to HER2/ErbB2 inhibitors [25], which could suggest that Hunk participates in a positive feedback loop to regulate EGFR activation.…”
Section: Intracellular Functions Of Hunkmentioning
confidence: 99%
“…Multiple lines of investigation demonstrated that targeting Hunk, either by shRNA knockdown in MMTV- neu -derived mammary tumor cells and HER2 + /ErbB2 + breast cancer cells, or through the use of MMTV- neu -genetically engineered mouse models bred into a Hunk −/− background, significantly impaired tumor growth [13, 24, 25]. It was also reported that a kinase-dead mutant of Hunk impaired tumor growth [24], suggesting Hunk kinase activity is important for the promotion of HER2 + /ErbB2 + mammary tumorigenesis in vivo.…”
Section: Hunk Is Implicated In Her2+/erbb2+ Breast Cancer and Devementioning
confidence: 99%
See 1 more Smart Citation